IMPROVEMENT OF METROLOGY SOFTWARE TEST IN COMPUTER SYSTEMS OF TEMPERATURE MEASUREMENT - Vasylkiv, Nadiya (International Journal of Computing, 2010)
In this paper the improved metrology software test is described by simulation the growth process of thermocouple thermoelectric heterogeneity acquired in operation conditions. It’s aimed to create the possibilities for the metrological studies of the temperature measuring channel in the computer measurement and control systems as well as a correction of the error caused by the thermocouple thermoelectric heterogeneity.